Memahami Hipotesis dan Contoh Pengujiannya - Maulidiyah Nur; Riska Putri Junita; Zulpan; Arianto (Indo Publishing, 2025)
This study aims to describe the formulation of statistical hypotheses in research hypothesis testing. Errors in the formulation of statistical hypotheses can create a very high risk for researchers to draw incorrect conclusions. The data sources of this library research are written documents such as books, journals, and other literature related to the formulation of statistical hypotheses. The author collected data using documentation techniques. The steps include reading the data sources, taking notes related to the research from those sources, and then processing the collected data. The data analysis techniques used are content analysis and descriptive analysis. In order for the research hypothesis proposed by the researcher to be tested statistically, it must first be translated into mathematical statements, which are called statistical hypotheses. The formulation of a research hypothesis into a statistical hypothesis follows very strict rules. Statistical hypotheses are divided into two types: the null hypothesis, formulated using the relation symbol “=”, and the alternative hypothesis, formulated using the symbols “>”, “<”, or “≠”. For example: (1) Right-tailed test: H₀: μ = μ₀, Hₐ: μ > μ₀; (2) Left-tailed test: H₀: μ = μ₀, Hₐ: μ < μ₀; (3) Two-tailed test: H₀: μ = μ₀, Hₐ: μ ≠ μ₀. The researcher obtained data from library sources or written documents such as journals, reference books, and other supporting literature. The purpose of this study is to address a phenomenon by formulating a conceptual solution through an in-depth review of the formulation of statistical hypotheses from various references. Therefore, this study employs a library research method, with primary data sources consisting of statistical books discussing hypothesis formulation, as well as supporting journals and literature. The data collection technique used is documentation, which includes reading data sources, recording relevant information, and processing the collected data. For data analysis, the researcher applies content analysis to understand the context of the literature related to statistical hypothesis formulation, and descriptive analysis to explain the findings based on the reviewed books and references.